Clarks ‘star’ advertisements of the 1940s: Classificatory terms and practices of historical interpretation - McDowell, Felice (Film, Fashion & Consumption, 2014)
Abstract In a number of studies that look at the cultural history of post-war Britain, class is referred to and used as a concept and a theoretical model of analysis. This article discusses aspects of the interdependent relationship between class, consumption, film and fashion in its analysis of a Clarks shoes advertising campaign from the 1940s, which featured an array of contemporary and mostly British actresses of both screen and stage. Unpacking how these elements work together in a network of meanings and values, this article suggests that the ways in which these various actresses are grouped together and represented in the branding of Clarks shoes is a process and practice of classification. Here, amongst other things, the actresses are defined by their ‘work’ and ‘labour’. By questioning how these elements also work to classify and categorize the actresses, this article invites alternative ways to think about and employ the concept of ‘class’ in practices of historical interpretation.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9mZmMuMy4zLjI0MV8x